2006
DOI: 10.1097/01.rli.0000187166.43871.fb
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intrarenal Oxygenation at 3.0 T Using 3-Dimensional Multiple Gradient-Recalled Echo Sequence

Abstract: Objective-The objective of this study was to validate quantitation of R 2 * and ΔR 2 * measurements obtained with a 3-dimensional (3-D) multiple gradient-recalled echo (mGRE) sequence for evaluating intrarenal oxygenation in humans.Materials and Methods-Validation was accomplished (1) by comparing R 2 * values with previously established 2-D techniques (n = 5, mean age = 33.6 years) and (2) by measuring change in ΔR 2 * after furosemide (20 mg intravenously) administration (n = 5, mean age = 22 years). Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
5
19
0
Order By: Relevance
“…FST has been utilized in acute kidney injury, measuring urine output over 2-4 h as the response to its administration [43,44]. Evaluating responses with BOLD MRI can demonstrate faster responses, typically within 15 min [45]. The recent study that reported increased cortical R2* to be associated with loss of renal function [26], found no association of response to furosemide with eGFR_slope.…”
Section: Discussionmentioning
confidence: 96%
“…FST has been utilized in acute kidney injury, measuring urine output over 2-4 h as the response to its administration [43,44]. Evaluating responses with BOLD MRI can demonstrate faster responses, typically within 15 min [45]. The recent study that reported increased cortical R2* to be associated with loss of renal function [26], found no association of response to furosemide with eGFR_slope.…”
Section: Discussionmentioning
confidence: 96%
“…Blood oxygenation level-dependent (BOLD) magnetic resonance imaging (MRI) has been shown to be very useful in monitoring intrarenal oxygenation. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] A major advantage of the noninvasive BOLD MRI is the ability to perform similar measurement in humans.…”
mentioning
confidence: 99%
“…Recent studies have used this improvement for renal BOLD magnetic resonance imaging, which appears more efficacious at 3 T compared to 1.5 T [23][24][25]. T2-prepared SSFP BOLD imaging is based on an endogenous contrast and does not need additional exogenous contrast agents.…”
Section: Discussionmentioning
confidence: 97%